2010
DOI: 10.1186/1751-0759-4-23
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes of GPs in Saxony-Anhalt concerning the Psychological Aspects of Bronchial Asthma: A Questionnaire Study

Abstract: Bronchial Asthma is a worldwide condition with particularly high prevalence in first world countries. The reasons are multifactorial but a neglected area is the psychological domain. It is well known that heavy emotions can trigger attacks and that depression negatively affects treatment outcomes. It is also known that personality type has a greater effect on disease prevalence than in many other conditions. However, many potential psychological treatments are hardly considered, neither in treatment guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This is important, as currently there is a lack of information on the associations between psychosocial work stress, measured by the demands-control-support model, and asthma. In Germany, for instance, 80% of general practitioners consider stress has an important role in the etiology of asthma, but only 11% refer their patients for psychological help ( Reed, Adolf, Werwick, & Herrmann, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is important, as currently there is a lack of information on the associations between psychosocial work stress, measured by the demands-control-support model, and asthma. In Germany, for instance, 80% of general practitioners consider stress has an important role in the etiology of asthma, but only 11% refer their patients for psychological help ( Reed, Adolf, Werwick, & Herrmann, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The studies showed that moderate to severe asthma has led to a worseQuality of Life (QoL) compared to mild persistent asthma (Stagi, 2018). The quality of life in asthmatics w a s r e p o r t e d t o g e t w o r s e w h e n it coexists with anxiety and/or depression (Moussavi et al, 2007;Moussas et al, 2008;Reed et al, 2010). A literature review of various studies related to impact of asthma on quality of life is necessary to put the impacts in proper perspective.…”
Section: Inroductionmentioning
confidence: 99%
“…Research published during the last few decades illustrates that psychological disorders are more common in individuals having bronchial asthma, especially if it is poorly controlled [ 14 , 15 ]. For instance, children with asthma are more likely than children without asthma to have anxiety and depression [ 16 - 19 ].…”
Section: Reviewmentioning
confidence: 99%